2009
DOI: 10.1521/jaap.2009.37.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to a Symposium: The God Representation in the Psychoanalytic Relationship: When is Three a Crowd?

Abstract: An introduction is presented to a symposium discussing the way in which the representation of the image of God can affect the analytic dialogue and process, focusing on the beliefs and images of the analyst as well as the analysand. If, as theorized, an image or a concept identified as "God" is an ineluctable element of the development of the human mind (whatever else this image may or may not mean theologically), then it would seem that the dynamic roots and potential of this kind of representation would find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Nevertheless, the ghost of Freud made the full exploration of religion and spirituality a taboo in the minds of many analysts (Sorenson, 2004). Fortunately, that perspective is changing in both contemporary psychoanalytic theory building (e.g., Hoffman, 2011;Rizzuto, 2009;Spero & Cohen, 2009) and in practice. For example, in discussing the results of her study of U.S. training analysts, Bartoli (2003) noted changes in attitudes since Freud's time and concluded that the majority of the participants were "quite appreciative of the patient's religious involvement when it allowed for flexibility in its theological tenets and when it was growth-promoting for their patients" (p. 364).…”
Section: Assumptions When Addressing Religion and Spirituality In Psy...mentioning
confidence: 99%
“…Nevertheless, the ghost of Freud made the full exploration of religion and spirituality a taboo in the minds of many analysts (Sorenson, 2004). Fortunately, that perspective is changing in both contemporary psychoanalytic theory building (e.g., Hoffman, 2011;Rizzuto, 2009;Spero & Cohen, 2009) and in practice. For example, in discussing the results of her study of U.S. training analysts, Bartoli (2003) noted changes in attitudes since Freud's time and concluded that the majority of the participants were "quite appreciative of the patient's religious involvement when it allowed for flexibility in its theological tenets and when it was growth-promoting for their patients" (p. 364).…”
Section: Assumptions When Addressing Religion and Spirituality In Psy...mentioning
confidence: 99%
“…We were interested in those experiences that did not emerge with ease, that are rare or completely novel, the surprising appearance at the periphery of consciousness of something uncanny yet all-too-familiar. 3 Obviously, our symposium required more than conscious compliance with the questions we posed (listed in the Introduction, Spero & Cohen, 2009). In essence, we were wondering whether our authors would be able to reveal themselves in the process of coming to grips with their own religious sentiments or imagery that surface during these moments of intensity and whether they would be able to distill the deeper relevance of their intuitions for the patient's unimagined realities.…”
mentioning
confidence: 99%
“…In the discussion that follows, we shall explore whether the expectations we delineated in the introduction to this symposium (Spero & Cohen, 2009) were practicable and to what degree did they elucidate old problems or highlight new ideas.…”
mentioning
confidence: 99%